NDMA formation mechanism by chloramination of tertiary amines - Le Roux, J.; Gallard, H.; Croue, Jean-Philippe; Papot, S.; Deborde, M. (2012)
Chloramination is used to reduce the formation of regulated disinfection by-products (i.e. trihalomethanes and haloacetic acids), or to avoid biofouling of membranes during wastewater reclamation processes. However, chloramination favors the formation of N-nitrosodimethylamine (NDMA), a human carcinogen. Proposed NDMA formation mechanisms used dimethylamine as a model precursor, but some anthropogenic tertiary amines presenting dimethylamine (DMA) functional groups have been demonstrated to lead to important amounts of NDMA (e.g. the pharmaceutical ranitidine). In this study, the mechanisms of NDMA formation by chloramination of tertiary amines (including model compounds presenting aromatic or heterocyclic rings, e.g. (dimethylaminomethyl)furfuryl alcohol (DFUR) or ranitidine) were studied. Compounds presenting heterocyclic rings substituted with DMA functions (e.g. DFUR, ranitidine) show much higher conversion rates to NDMA than other tertiary amines or DMA. A mechanism is proposed to explain the high yields of NDMA obtained from the decomposition of these tertiary amines during chloramination. This mechanism is based on the production of a carbocation intermediate formed from the methylated aromatic moieties present in the compounds, favouring the release of NDMA. © 2012 American Water Works Association AWWA WQTC Conference Proceedings.